Redesigning Health Care in ECA : Some Lessons from the UK - Marquez, Patricio; Chalkidou, Kalipso; Cutler, Derek; Doyle, Nick (World Bank, Washington, DC, 2012)
The countries in Europe and Central Asia (ECA) have been struggling to deliver good, affordable health care to their populations. Indeed, life expectancy gains in the region have been significantly lower than in other middle or high-income countries, and in some ECA countries the relative low level of public sector funding to cover the cost of free medical care that is already promised by the governments to their citizens has consistently hindered access to quality services and led to a significant increase in out-of-pocket spending by patients for healthcare. The main challenge now is to redesign health systems to effectively address the changing health needs of the population, chiefly the increase in non-communicable diseases such as cardiovascular diseases, cancer, and injuries, as the leading causes of ill-health, premature mortality and disability.